The role of the stem cell epigenome in normal aging and rejuvenative therapy - Jayarajan, Jeyan; Milsom, Michael (Human molecular genetics, 2020)
Adult stem cells are ultimately responsible for the lifelong maintenance of regenerating of tissues during both homeostasis and following injury. Hence, the functional attrition of adult stem cells is thought to be an important driving factor behind the progressive functional decline of tissues and organs that is observed during aging. The mechanistic cause underlying this age-associated exhaustion of functional stem cells is likely to be complex and multifactorial. However, it is clear that progressive remodeling of the epigenome and the resulting deregulation of gene expression programs can be considered a hallmark of aging, and is likely a key factor in mediating altered biological function of aged stem cells. In this review, we outline cell intrinsic and extrinsic mediators of epigenome remodeling during aging; discuss how such changes can impact on stem cell function; and describe how resetting the aged epigenome may rejuvenate some of the biological characteristics of stem cells.
Gesehen am 02.04.2022